Review of knowledge, attitude, and practice among laboratory workers towards occupational safety and health - Almutairi, Nayef Shabbab; Mohd Tamrin, Shamsul Bahri; Ng, Yee Guan; How, Vivien (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Laboratory workers exposed to diverse occupational exposures to accidents. Evidently, extant, yet very limited empirical underpinnings suggest that knowledge, practices and awareness of safety precautions are uncharacteristically poor among laboratory workers. As such, their demonstration of safety-related attitudes and practices have remained questionable. This paper, thus presents a systematic search of the literature on laboratory workers’ safety-related knowledge, attitudes, and practices. Specifically, literature published between 2007 and 2017 that characteristically attempted to evaluate knowledge, attitudes and practices among laboratory workers on Occupational Safety and Health were reviewed. Evidently, results from the review indicate poor knowledge, attitude and practice among the laboratory workers. It is critical that strategies be put in place by the management of the health facilities to institute and undertake activities in the form of training, improved safety management practices, organizational commitment and improved safety culture.